PENGARUH POPULASI DAN PEMBERIAN PUPUK BIO SLURRY KOTORAN SAPI PADA PERTUMBUHAN DAN HASIL TANAMAN OKRA (Abelmoschus Esculentu L. Moench) - Taufiq Nurrohman, Adi (Universitas Islam Balitar, 2019)
This study aims to 1) To determine the interaction of organic fertilizers and plant spacing on the growth and production of okra plants. 2) To determine the best dose of organic fertilizer on the growth and production of okra plants. 3) To determine the appropriate planting spacing for the growth and production of okra plants. This research was conducted using factorial randomized block design (RBD) with 2 factors, the first factor was plant spacing (A) consisting of 3 levels, namely: 60x40 cm (A1), 60x50 cm (A2), 60x60 cm (A3) . The second factor was the dose of organic fertilizer (J) which consists of 3 levels, namely 5 tons / ha-1 (J1), 10 tons ha-1 (J2), 15 kg ha-1 (J3). The variables observed included plant height, stem diameter, number of leaves, total pods, total pod weight and pod quality. Data were analyzed using analysis of variance (ANOVA) level of 5% and further testing with Duncan's Multiple Range Test (DMRT). The results showed that: There was no significant interaction between organic fertilizer dosage and plant spacing on the growth and production of okra plants. Dosage treatment of organic fertilizer Bio slurry 15 Ton ha-1 (A3) significantly affected plant height, stem diameter, the highest plant height of 55.6411, 72.5322 and 77.0889 at the age of 6.7 and 8 MST. The highest stem diameter is 0.8689, 1.7844, 2.1289, 2, 0789 at the age of 3,6,7 and 8 MST. the best number of leaves is 27,706 age 8 MST. The treatment of plant spacing of 60x40 cm (A1) had a significant effect on the total number of pods and total pod weight, the total number of pods was 23.8569 and the total pod weight was 275.85 g in all harvests